I libretti italiani a Vienna tra Sei e Settecento = Italian Libretti in Vienna During the Seventeenth and Eighteenth Centuries (Böhlau, 2025)
The present collection of essays focusing on Italian librettos at the Habsburg Court during the Baroque era gathers together the papers presented at the international conference “I libretti italiani a Vienna tra Sei e Settecento” (University of Vienna 2019). It aims at stimutaling and renewing the debate on a topic that still needs that appropriate attention among the fields of study related to the modern age. Der vorliegende Band umfasst Studien zum italienischen Libretto am habsburgischen Hof im Barock, die in Vorträgen bei einer internationalen Konferenz an der Universität Wien im Juni 2019 vorgestellt wurden, und hat das Ziel, weitere Fragestellungen zu diesem für kulturwissenschaftliche Studien der Frühen Neuzeit hochinteressanten Themengebiet anzuregen und anzustoßen.